PERBANDINGAN PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN PROJECT BASED LEARNING (PJBL) TERHADAP MOTIVASI DAN KETERAMPILAN MENULIS DESKRIPSI PADA MURID KELAS V GUGUS II KECAMATAN MAMAJANG KOTA MAKASSAR - Azizha, Rifiatul; Sulfasyah; Rimang, Siti Suwada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research discusses the comparison of Problem Based Learning (PBL) and Project Based Learning (PJBL) learning models on motivation and descriptive writing skills in class V students of Gugus II, Mamajang District, Makassar City. This research aims to analyze the differences in motivation and writing skills taught using the PBL and PJBL models. The type of research used is quantitative experimental research Posttest-Only Control Design. The population in this study were all class V students of Gugus II, Mamajang District, totaling 6 schools with a total number of students of 272. The research sample was class V students of UPT SPF SD Negeri Labuang Baji II, totaling 45 people who were selected using random sampling techniques, which comes from 2 classes, namely VA using PBL and VB using PJBL. Data collection techniques are questionnaire techniques to determine learning motivation and tests to determine students' writing skills. The research results based on descriptive analysis showed that the average value of the PBL learning motivation questionnaire was 87.79 while PJBL was 81.42. on PBL description writing skills is 94.26 while PJBL is 81.23. This means that the average value of PBL motivation and writing skills is higher than PJBL. The results of the inferential analysis show that the PBL learning model has a more significant effect compared to the PJBL learning model on the motivation and descriptive writing skills of class V UPT SPF students at SD Negeri Labuang Baji II. This is based on the MANOVA test results obtained, namely the sig value. 0.01 < 0.05.